Transmission of COVID-19 from community to healthcare agencies and back to community: a retrospective study of data from Wuhan, China - Xiaoqi Zhou; Yan Guo; Mei Yang; Yaqiong Yan; Anshu Li; Gengchen Xie; Yanhui Pang; Qiman Jin; Juan Dai; Xinghua Liu (BMJ Open)
Background The early spatiotemporal transmission of COVID-19 remains unclear. The community to healthcare agencies and back to community (CHC) model was tested in our study to simulate the early phase of COVID-19 transmission in Wuhan, China.Methods We conducted a retrospective study. COVID-19 case series reported to the Municipal Notifiable Disease Report System of Wuhan from December 2019 to March 2020 from 17 communities were collected. Cases from healthcare workers (HW) and from community members (CM) were distinguished by documented occupations. Overall spatial and temporal relationships between HW and CM COVID-19 cases were visualised. The CHC model was then simulated. The turning point separating phase 1 and phase 2 was determined using a quadratic model. For phases 1 and 2, linear regression was used to quantify the relationship between HW and CM COVID-19 cases.Results The spatial and temporal distributions of COVID-19 cases between HWs and CMs were closely correlated. The turning point was 36.85±18.37 (range 15–70). The linear model fitted well for phase 1 (mean R2=0.98) and phase 2 (mean R2=0.93). In phase 1, the estimated α^s were positive (from 18.03 to 94.99), with smaller β^s (from 2.98 to 15.14); in phase 2, the estimated α^s were negative (from −4.22 to −81.87), with larger β^s (from 5.37 to 78.12).Conclusion Transmission of COVID-19 from the community to healthcare agencies and back to the community was confirmed in Wuhan. Prevention and control measures for COVID-19 in hospitals and among HWs are crucial and warrant further attention.